La música como recurso para el desarrollo del lenguaje oral en los niños de 4 a 5 años. - Soria Tipanluisa, Sonia Elizabeth (2022)
The present investigation arises from the problem detected in the "Pujilí" Educational Unit, of the Pujilí Canton, where the importance of Linguistic Awareness and its influence on the development of oral language of children from 4 to 5 years old was diagnosed by the authors Chuqui Saquinga Lourdes Conzuelo & Suquilanda Japan Martha Alexandra, the problem was generated by the lack of information and application that the teachers have about them to be executed correctly in the development of the children's oral language, who used the qualitative approach together with the use of the inductive method. For this reason, the proposal "Music as a resource in the development of oral language in children aged 4 to 5 years" was proposed, to respond to the problem detected, it is proposed as a general objective: Design musical resources for the development of oral language in children. 4-5 years old in the Pujilí Educational Unit. Ten workshops were held under the name "The magic of music makes me speak", the same ones that will strengthen oral language, body expression, abilities, skills and linguistic awareness, through recreational activities, educational content and children's songs, with the purpose of guiding the children of the institution to improve the development of oral language that will later be applied for the socialization of the child. The constructivist pedagogical approach was used where the cognitive, procedural and affective aspects are developed, emphasizing that in this model children learn by doing, that is, constantly interacting with the different tangible and intangible objects in the environment. The proposal was validated by experts and users who rated it as Totally Good, with each of the musical resources being of importance. The proposed workshops have a fundamental educational impact that will favor the development of oral language in the children of the Pujilí Canton, activities such as resources can be replicated in different educational units, contributing to the educational development of children.